PENGARUH REWARD DAN PUNISHMENTTERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X IPS SMA NEGERI 1 ULAKAN TAPAKIS KABUPATEN PADANG PARIAMAN - Hasnan Nafis (Ensiklopedia Education Review, 2022)
The background of this research is the existence of problems regarding Reward and Punishment with the economics learning outcomes of class X.IPS SMAN 1 Ulakan Tapakis. this is caused by several factors that are thought to be the cause of low learning outcomes including the provision of Rewards and Punishment, as evidenced in the learning process observed by the authors including: First, the teacher only conveys material without being interspersed with giving rewards such as smiles, laughter, and praise. Second, there is no Punishment given to students who are still walking around borrowing pens from their friends for reasons of forgetting to bring pens even though the lesson has already started. Third, giving the same Punishment repeatedly as found by the author when making observations outside the classroom, students who are late are punished for picking up trash, this punishment is carried out every day so that it does not have a deterrent effect seen from the same students who are late again the next day.This type of research is a correlational study consisting of two variables. The sampling technique used a total sampling technique where the entire population was sampled as many as 96 students. The research instrument used was a questionnaire. The data analysis technique used to test the hypothesis is the T test and F test.Based on the partial reward statistical test (X1) on learning outcomes, the value of tcount > ttable (2.260 > 1.667) with a significant value of 0.026 <0.05 means that Ha is accepted and H0 is rejected. This means that reward affects the results of learning economics. Partially Punishment (X2) on learning outcomes is obtained (2.299 > 1.667) with a significant value of 0.024 <0.05 which means Ha is accepted and H0 is rejected. This means that Punishment has an effect on economic learning outcomes. While simultaneously Fcount > Ftable (5.720 > 3.09), with a significant value (0.005 <0.05) and a contribution of 100% which means Ha is accepted and H0 is rejected which means Reward and Punishment simultaneously have a positive and significant effect on economic learning outcomes .Keywords: Reward, Punishment, Learning outcomes